2004
DOI: 10.1084/jem.20031080
|View full text |Cite
|
Sign up to set email alerts
|

c-FLIP Mediates Resistance of Hodgkin/Reed-Sternberg Cells to Death Receptor–induced Apoptosis

Abstract: Resistance to death receptor–mediated apoptosis is supposed to be important for the deregulated growth of B cell lymphoma. Hodgkin/Reed-Sternberg (HRS) cells, the malignant cells of classical Hodgkin's lymphoma (cHL), resist CD95-induced apoptosis. Therefore, we analyzed death receptor signaling, in particular the CD95 pathway, in these cells. High level CD95 expression allowed a rapid formation of the death-inducing signaling complex (DISC) containing Fas-associated death domain–containing protein (FADD), cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
160
2
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(184 citation statements)
references
References 64 publications
16
160
2
5
Order By: Relevance
“…34,35 Several studies have shown that functional blockade of antiapoptotic factors can either restore the apoptotic process in tumor cells or sensitize them to chemotherapy-and death ligand-induced apoptosis. 36,37 Accordingly, we showed that cancer cells express high levels of the antiapoptotic proteins PED/PEA-15, cFLIP, Bcl-xL and Bcl-2. This finding may explain why cancer cells despite expressing high levels of TRAIL-R1/R2 are refractory to apoptosis induction, even in the presence of high concentrations of a highly active recombinant form of TRAIL, and why at the same time they are resistant to the effects of conventional chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Several studies have shown that functional blockade of antiapoptotic factors can either restore the apoptotic process in tumor cells or sensitize them to chemotherapy-and death ligand-induced apoptosis. 36,37 Accordingly, we showed that cancer cells express high levels of the antiapoptotic proteins PED/PEA-15, cFLIP, Bcl-xL and Bcl-2. This finding may explain why cancer cells despite expressing high levels of TRAIL-R1/R2 are refractory to apoptosis induction, even in the presence of high concentrations of a highly active recombinant form of TRAIL, and why at the same time they are resistant to the effects of conventional chemotherapeutic drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that FLIP promotes resistance to chemotherapy, as FLIP gene silencing enhanced chemotherapy-induced cell death in vitro, and FLIP L overexpression conferred resistance to chemotherapeutic agents both in vitro and in vivo (Longley et al, 2006;Wilson et al, 2007). We and others have found that FLIP overexpression renders cells resistant to death ligands (Jonsson et al, 2003;Longley et al, 2006), whereas FLIP downregulation increases sensitivity (Yeh et al, 2000;Mathas et al, 2004;Galligan et al, 2005;Longley et al, 2006). Cell lines are classified as type I or II depending on whether they require mitochondrial involvement to induce apoptosis following death receptor activation.…”
Section: Discussionmentioning
confidence: 59%
“…The role of FLIP as a key regulator of death ligandinduced apoptosis is well established (Yeh et al, 2000;Mathas et al, 2004). We have demonstrated previously that silencing FLIP induces apoptosis in a panel of colorectal cancer cell lines in a manner that is dependent on caspase 8 and DR5, but that appears to be independent of DR5 ligation by TRAIL (Wilson et al, 2007).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the enhanced chemoresistance in the c-FLIP L -overexpressing lines may be due at least in part to c-FLIP L -activating intrinsic survival pathways such as those mediated by NF-kB and PI3 kinase Kataoka and Tschopp, 2004). Several studies have demonstrated that downregulating c-FLIP sensitizes various tumour cells to apoptosis induced by Fas agonists and TRAIL (Fulda et al, 2000;Poulaki et al, 2002;Mathas et al, 2004;Santiago et al, 2004). However, we are aware of only one other study that has demonstrated that downregulating c-FLIP sensitizes cancer cells to chemotherapy in the absence of cotreatment with a death receptor ligand.…”
Section: Discussionmentioning
confidence: 99%